Impact of perioperative chemotherapy on survival in patients with advanced primary urethral cancer: results of the international collaboration on primary urethral carcinoma - Gakis, G; Morgan, T M; Daneshmand, S; Keegan, K A; Todenhöfer, T; Mischinger, J; Schubert, T; Zaid, H B; Hrbacek, J; Ali-El-Dein, B; Clayman, R H; Galland, S; et al. (Annals of oncology, 2015)
BACKGROUND: To investigate the impact of perioperative chemo(radio)therapy in advanced primary urethral carcinoma (PUC). PATIENTS AND METHODS: A series of 124 patients (86 men, 38 women) were diagnosed with and underwent surgery for PUC in 10 referral centers between 1993 and 2012. Kaplan-Meier analysis with log-rank testing was used to investigate the impact of perioperative chemo(radio)therapy on overall survival (OS). The median follow-up was 21 months (mean: 32 months; interquartile range: 5-48). RESULTS: Neoadjuvant chemotherapy (NAC), neoadjuvant chemoradiotherapy (N-CRT) plus adjuvant chemotherapy (ACH), and ACH was delivered in 12 (31%), 6 (15%) and 21 (54%) of these patients, respectively. Receipt of NAC/N-CRT was associated with clinically node-positive disease (cN+; P = 0.033) and lower utilization of cystectomy at surgery (P = 0.015). The objective response rate to NAC and N-CRT was 25% and 33%, respectively. The 3-year OS for patients with objective response to neoadjuvant treatment (complete/partial response) was 100% and 58.3% for those with stable or progressive disease (P = 0.30). Of the 26 patients staged ≥cT3 and/or cN+ disease, 16 (62%) received perioperative chemo(radio)therapy and 10 upfront surgery without perioperative chemotherapy (38%). The 3-year OS for this locally advanced subset of patients (≥cT3 and/or cN+) who received NAC (N = 5), N-CRT (N = 3), surgery-only (N = 10) and surgery plus ACH (N = 8) was 100%, 100%, 50% and 20%, respectively (P = 0.016). Among these 26 patients, receipt of neoadjuvant treatment was significantly associated with improved 3-year relapse-free survival (RFS) (P = 0.022) and OS (P = 0.022). Proximal tumor location correlated with inferior 3-year RFS and OS (P = 0.056/0.005). CONCLUSION: In this series, patients who received NAC/N-CRT for cT3 and/or cN+ PUC appeared to demonstrate improved survival compared with those who underwent upfront surgery with or without ACH.
Keywords: diverze moči; Albumin-Bound Paclitaxel; uretra; spinocelulární karcinom; Cisplatin; lidé; Middle Aged; Mitomycin; Deoxycytidine; Female; Chemoradiotherapy; Urinary Diversion; Ifosfamide; Chemotherapy, Adjuvant; paklitaxel vázaný na albumin; retrospektivní studie; Perioperative Care; perioperační péče; Humans; neoadjuvantní terapie; protokoly protinádorové kombinované chemoterapie; Carboplatin; adenokarcinom; Cystectomy; fluoruracil; Carcinoma, Squamous Cell; Carcinoma, Transitional Cell; lidé středního věku; přežití bez známek nemoci; Fluorouracil; mužské pohlaví; cisplatina; chemoradioterapie; mitomycin; karboplatina; ifosfamid; paclitaxel; ženské pohlaví; adjuvantní chemoterapie; Kaplanův-Meierův odhad; Disease-Free Survival; cystektomie; Kaplan-Meier Estimate; karcinom z přechodných buněk; nádory močové trubice; Aged; Male; Paclitaxel; Adenocarcinoma; Retrospective Studies; Neoadjuvant Therapy; Urethral Neoplasms; Antineoplastic Combined Chemotherapy Protocols; Urethra; deoxycytidin; senioři